Making a greener planet: nature documentaries promote plant awareness. (16th February 2023) - Kacprzyk, Joanna; Clune, Stephanie; Clark, Clare; Kane, Adam
Abstract: Background and Aims: Plants underpin life on Earth and are essential to human existence. Alarmingly, almost 40% of plant species are under threat of extinction, with plants that are not directly useful to humans being particularly vulnerable. Plant diversity and its untapped resources require urgent protection to safeguard our future, but conservation initiatives are biased towards mammals and birds. Plant awareness disparity, formerly known as plant blindness, describes our tendency to ignore plant life and has been suggested to play a crucial role in the bias against funding and support for plant conservation programmes. Previous studies indicate that nature documentaries can generate shifts in audience awareness of animal species by providing vicarious connections to nature. Here, we investigated whether the plant-focused popular BBC show Green Planet had a similar effect for plants and stimulated audience engagement for information after the broadcast. Methods: Online searches for further information were considered a form of engagement for evaluation of the interest of the audience in plants portrayed in Green Planet episodes. The big data activities (Google search engine and Wikipedia pageviews trends) related to the plants mentioned in Green Planet episodes were examined over the period covering the broadcast of the show in UK. Key Results: Analyses indicate that Green Planet generated increased awareness and stimulated audience engagement for further information about plants featured in the show, with audience reaction driven by the screen time. Conclusions: Natural history films can promote plant awareness, and culturomic tools can be used to assess their impact on the general public, potentially also to inform plant conservation strategies. These are promising findings as we strive to increase public awareness of the value of plant life.